2016
DOI: 10.13005/bbra/2018
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Status of Aedes aegypti to Insecticides in the Jazan Region of Saudi Arabia

Abstract: The present study was designed to provide information on the susceptibility status of the adult and larvae of Aedes aegypti mosquitoes in Jazan region of Saudi Arabia. Bioassay tests were performed on adults and larvae by using WHO recommended concentrations and test kits. Adults of Ae. aegypti mosquitoes were exposed to test papers impregnated with Lambda-cyhalothrin (0.05%), Cyfluthrin (0.15%), Deltamethrin (0.05%), Permethrin (0.75%), Fenitrothion (1%), Bendiocarb (0.1%) and DDT (4%) insecticides. Ae. aegyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…aegypti population genetic structure. In common with previous reports from Jazan province [11], Makkah and Jeddah strains showed high resistance to carbamate (benidocarb), but mortality following exposure to the organophosphate fenitrothion was only slightly reduced.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…aegypti population genetic structure. In common with previous reports from Jazan province [11], Makkah and Jeddah strains showed high resistance to carbamate (benidocarb), but mortality following exposure to the organophosphate fenitrothion was only slightly reduced.…”
Section: Discussionsupporting
confidence: 87%
“…aegypti has now been detected around the globe with reports from Brazil, Mexico, Thailand, China, Grand Cayman, Latin America, Indonesia and Malaysia [26]. Reports of resistance from the Middle-Eastern region involve studies from the Ibb region of Yemen [36], from Jazan in Saudi Arabia [11] approximately 500 km north, and from Makkah [10], a further 700 km north. WHO bioassay results in each case were similar, with mortalities ranging from 75–93% to different pyrethroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti to cyfluthrin was100%. Similar findings were obtained in a previous study from the Jazan region (15). However, our finding was greater than that previously reported from Mecca (90%) (16).…”
Section: Discussionsupporting
confidence: 88%
“…Few studies have been reported on the resistance status of Ae. aegypti to insecticides in Saudi Arabia (15)(16)(17). Furthermore, studies on mechanisms of resistance to pyrethroids in Ae.…”
Section: Research Articlementioning
confidence: 99%